Infectious adverse events associated with immune checkpoint inhibitors: a pharmacovigilance analysis based on FAERS database - Song, Suting; Yang, Yana; Hu, Qu; Zhong, Rongjie; Lei, Xuejiao; Wang, Chunyu; Wang, Ying; Luo, Yan (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) have revolutionized cancer treatment, but their association with infectious adverse events (iAEs) remains incompletely characterized. These infections may arise from immune dysregulation or immunosuppressive therapies used to manage immune-related toxicities, posing significant clinical challenges. This study aims to define the spectrum, proportion, timing, and clinical outcomes of iAEs in patients treated with ICIs.MethodData from the first quarter of 2011 to the fourth quarter of 2023 in FAERS database were extracted to conduct disproportionality analysis. Two signal indices, the reporting odds ratio (ROR) and the information component (IC), which are based on statistical shrinkage transformation, were used to evaluate the correlations between ICIs and immune-related iAEs. Evaluated regimens included ICI monotherapy and combination therapies. Infectious AEs were classified by high-level group terms (HLGTs), high-level terms (HLTs), and preferred terms (PTs) based on the Medical Dictionary for Regulatory Activities (MedDRA), then ranked by frequency and signal strength.ResultsAmong 147,854 reports of irAEs, we identified 18068 iAEs demonstrating an overall elevated infection risk (ROR = 1.08, 95% CI [1.07-1.10]) with profound agent-specific heterogeneity. Atezolizumab (ROR = 1.45) and cemiplimab (ROR = 1.42) exhibited the highest risks, while pembrolizumab was associated with a lower risk of iAEs (ROR = 0.82). Disproportionality analyses revealed significant signals for bacterial pneumonia (ROR = 7.49), clostridioides difficile colitis (ROR = 2.11), and pneumocystis jirovecii pneumonia (ROR = 3.78), with pathogen-confirmed cases distributed as bacterial (11.67%), viral (12.20%), and fungal (4.57%) etiologies. Temporal analysis established a critical vulnerability window wherein >70% of iAEs manifested within three months of ICI initiation (median onset 40 days), with pembrolizumab demonstrating the shortest latency (27 days). Age-related disparities revealed that advanced age is associated with increased risk of iAEs following ICI therapy. Combination regimens amplified specific risks, notably encephalitis for nivolumab-ipilimumab (ROR = 17.72), while hospitalization rates reached 71.23% for ipilimumab monotherapy.ConclusionsThis study highlights the significant risk of iAEs in patients treated with ICIs, emphasizing the need for vigilant monitoring, particularly in older patients and those receiving combination therapies. Tailored strategies to prevent and manage infections are essential, and further research is necessary to better understand the mechanisms underlying these adverse events and to refine therapeutic approaches.